1991
DOI: 10.1590/s0037-86821991000100003
|View full text |Cite
|
Sign up to set email alerts
|

Biting behavior of Anopheles mosquitoes in Costa Marques, Rondonia, Brazil

Abstract: Mosquito collections were made in and near

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1
11

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 7 publications
5
41
1
11
Order By: Relevance
“…darlingi was much more abundant in anthropic environments. Although their study was made in a short period they confirmed the vector synanthropy of previous surveys made in the North Region 13,17,18,33 . Anopheles albitarsis s.l.…”
Section: Discussionsupporting
confidence: 75%
“…darlingi was much more abundant in anthropic environments. Although their study was made in a short period they confirmed the vector synanthropy of previous surveys made in the North Region 13,17,18,33 . Anopheles albitarsis s.l.…”
Section: Discussionsupporting
confidence: 75%
“…darlingi reflect local differences in the availability of various types of larval habitats (creeks, strips of flooded forest, river edges and pools in river beds), in relation with both rainfall and river levels. In accordance with Klein & Lima (1990), we think that the effect of rainfall may be immediately apparent or have a lag time, depending on the type of larval habitat, and thus, the variations in adult abundance of An. darlingi are probably affected by a combination of biotic (quality of aquatic vegetation and fauna) and physical factors, such as temperature and humidity.…”
Section: Parous Rates and Vci -supporting
confidence: 67%
“…Como exemplos, os Municípios de Jarú, Ariquemes e Machadinho d 'Oeste registraram, em 1991, IPA nos valores de 203,7, 499,0 e 798,1, respectivamente (Escobar, 1994. Diante deste panorama, houve desenvolvimento de vários estudos visando ao conhecimento das espécies de mosquitos envolvidas na transmissão da malária na região (Deane et al, 1988;Klein & Lima, 1990;Lourenço-de-Oliveira et al, 1989;Tadei et al, 1988;Tadei et al, 1998). Foram identificadas diferentes espécies de Anopheles como potencialmente vetoras de Plasmodium sp.…”
unclassified